Bone health and high-performace athletes - Stewart, K. L. (Queensland University of Technology, 2020)
Physical activity is beneficial for bones. However, intense and repetitive training as experienced in elite sport creates situations in which bone health may be compromised. This thesis provides evidence of reduced bone mineral density, and increased risk of injury, in International level triathletes. Regional differences in bone mineral density were found in relation to sex and training volume. The outcomes of poor bone health in elite athletes can interrupt or prematurely end careers (stress fractures) and may endure into post-career life (osteoporosis). Athlete bone health, therefore, should be monitored regularly, particularly in those that compete in endurance sports.